Kellogg's six-hour day - Kline Hunnicutt, Benjamin (Philadelphia, 1996)
"On December 1, 1930, at the start of the Great Depression, W.K. Kellogg replaced the traditional three daily eight-hour shifts in his cereal plant with four six-hour shifts. By adding on a new shift he and his managers created jobs for employees that the company had laid off and for other unemployed persons in Battle Creek, Michigan.